Congenital prepubic sinus: A case report of local experience within a sub-Saharan setting - Olumide A. Elebute; Justina O. Seyi-Olajide; O. Akinjo; O. Alagbe; Felix Makinde Alakaloko; Adesoji O. Ademuyiwa; Christopher O. Bode (Journal of Clinical Sciences)
Congenital prepubic sinus is a rare congenital anomaly of the external genital organs, characterized by an opening on the dorsum with discharge of purulent material in most cases. The condition is not peculiar to males. The etiology behind this anomaly is still elusive, with some proposing that the anomaly is akin to urethral duplication. Immunochemistry findings revealing transitional epithelium in the mucosal lining of the sinus in some reports have corroborated this theory. We report two male pediatric cases. Each had a pustular-looking lesion on the dorsum of the penile shaft. The tracts were cannulated, skeletonized, and completely excised. The histological findings of stratified squamous epithelium were reported separately in our patients. Congenital prepubic sinus is a rare congenital penile lesion. A high index of suspicion is needed for diagnosis. The primary goal of treatment is to excise the entire tract to prevent recurrence.